A comparative evaluation of viewing metaphors on psychophysical skills education in an interactive virtual environment. Issue 3 (September 2016) - Parmar, Dhaval; Bertrand, Jeffrey; Babu, Sabarish; Madathil, Kapil; Zelaya, Melissa; Wang, Tianwei; Wagner, John; Gramopadhye, Anand; Frady, Kristin
Abstract In an empirical evaluation, we examined the effect of viewing condition on psychophysical skills education in an interactive 3D simulation to train users in electrical circuitry. We compared an immersive head-mounted display (HMD)-based viewing metaphor versus a limited, desktop-based virtual reality (DVR) viewing metaphor with interaction using a spatial user interface. Psychophysical skills education involves the association of cognitive functions with motor functions to make the task autonomous with repeated practice. In electrical circuitry, this is demonstrated by the fine movements involved in handling and manipulating components on the electrical circuit, particularly while measuring electrical parameters. We created an interactive circuitry simulation (IBAS) where participants could learn about electrical measurement instruments such as the ammeter, voltmeter and multimeter, in a simulated breadboard VR system. Twenty-four participants utilized the simulation (12 in each condition), and the quantitative and qualitative aspects of psychophysical skills education with respect to the viewing metaphor were examined. Each viewing condition in IBAS was head-tracked and non-stereoscopic. Perspective correction was coupled with head-tracking in the DVR condition. The key quantitative measures were cognitive questionnaires addressing different levels of Bloom's cognitive taxonomy and a real-world psychophysical task addressing various levels of Dave's psychomotor taxonomy. The qualitative measures were the Witmer–Singer sense of presence questionnaire and self-report. Results suggest that there was a significant increase in cognition post-experiment in both DVR and HMD viewing conditions in levels of knowledge, application, analysis and evaluation. Results also revealed a significant learning benefit with respect to the higher level concepts pertaining to evaluation in the HMD condition as compared to DVR. Participants seem to have enjoyed a greater level of affordance in task performance and spent a larger amount of time to complete the simulated exercises as well as manually maneuvered to further distances in the HMD viewing condition as compared to DVR viewing.